Final answer:
The quadratic equation with roots -4 and 2 is equivalent to x² - 2x + 8 = 0.
Step-by-step explanation:
If the roots of a quadratic equation are -4 and 2, then we can express the equation in its factored form as (t + 4)(t - 2) = 0. To find the equivalent quadratic equation, we simply expand this product:
t(t - 2) + 4(t - 2) = t² - 2t + 4t - 8 = t² + 2t - 8
Thus, the equation with roots -4 and 2 is t² + 2t - 8 = 0. This is the standard form of the quadratic equation at² + bt + c = 0, where the coefficients are a = 1, b = 2, and c = -8.